Effects of coronavirus disease 2019 (COVID-19) pandemic on antimicrobial prevalence and prescribing in a tertiary hospital in Singapore - Ng, Tat Ming (BioMed Central Ltd, 2022)
10.1186/s13756-021-00898-8